Análise geoespacial dos problemas socioambientais urbanos da zona de manguezal do município de Bayeux - PB e dos casos de hanseníase de 2001 a 2011 - Costa, Charliton Ferreira da (2013)
The urbanization process that occurred in the last few decades it's the source of many considerable concerns problems, correlated to ground occupation in the cities and their abuse. The great population concentration of economic ativities and the existing tecnologic patterns are increasing the urban environment degradation, being a consequence of lifestyle developtment that leads to predatory use of natural resources. Forests, lakes, rivers and mangrove are environments with natural particularities being constantly modified by inappropiate occupation. The brazilian mangroves have been highlighted when talked about intervetions, especially because of their localization, once that this ecosystem is found in the area with the biggest population concentration in Brazil, the coastal region. It's also worthy a note that relations between environment quality and infectocontagious diseases mortality are examples of studies with great value in the field of environmental health, because they want to identify and evaluate the impact of contrary environmental conditions about shortspam time period. Leprosy it's an infectocontagious disease, caused by bacterium called Mycobacterium leprae, of cronical evolution that spreads itself by cutaneous injuries with decrease of thermal, soreness and tactile sensibility. This disease is presented as a serious issue of public healthy in Brazil. In this case, this work has his aim in indetify the main environmental issues in consequence of urban occupation growth in the mangroves area and make a geospacial analisis of leprosy cases in the Bayeux city. This research used geoprocessing and revealed important results in relation to identification of the many serious problems of environmental order as also to find real leprosy cases in Bayeux, presenting itself, this way, as an important tool to implatation of appropriate policies and to social actions and campaigns head direction, that may intervene in a strong and positive maneer in the leprosy control at the studied city. Then, after the endemy spatial observation, it was possible to elucidate doubts when talking about the real localization of cases, showing and explaining that the leprosy cases are grouped in areas located at the north/central part of Bayeux city and a small number of cases located in near margin rivers, where the majority part of the low socioeconomic level population lives.